Resting Afferent Renal Nerve Discharge and Renal Inflammation: Elucidating the Role of Afferent and Efferent Renal Nerves in Deoxycorticosterone Acetate Salt Hypertension. Issue 6 (December 2016) - Banek, Christopher T.; Knuepfer, Mark M.; Foss, Jason D.; Fiege, Jessica K.; Asirvatham-Jeyaraj, Ninitha; Van Helden, Dusty; Shimizu, Yoji; Osborn, John W.
Abstract : Renal sympathetic denervation (RDNx) has emerged as a novel therapy for hypertension; however, the therapeutic mechanisms remain unclear. Efferent renal sympathetic nerve activity has recently been implicated in trafficking renal inflammatory immune cells and inflammatory chemokine and cytokine release. Several of these inflammatory mediators are known to activate or sensitize afferent nerves. This study aimed to elucidate the roles of efferent and afferent renal nerves in renal inflammation and hypertension in the deoxycorticosterone acetate (DOCA) salt rat model. Uninephrectomized male Sprague–Dawley rats (275–300 g) underwent afferent-selective RDNx (n=10), total RDNx (n=10), or Sham (n=10) and were instrumented for the measurement of mean arterial pressure and heart rate by radiotelemetry. Rats received 100-mg DOCA (SC) and 0.9% saline for 21 days. Resting afferent renal nerve activity in DOCA and vehicle animals was measured after the treatment protocol. Renal tissue inflammation was assessed by renal cytokine content and T-cell infiltration and activation. Resting afferent renal nerve activity, expressed as a percent of peak afferent nerve activity, was substantially increased in DOCA than in vehicle (35.8±4.4 versus 15.3±2.8 %Amax). The DOCA–Sham hypertension (132±12 mm Hg) was attenuated by ≈50% in both total RDNx (111±8 mm Hg) and afferent-selective RDNx (117±5 mm Hg) groups. Renal inflammation induced by DOCA salt was attenuated by total RDNx and unaffected by afferent-selective RDNx. These data suggest that afferent renal nerve activity may mediate the hypertensive response to DOCA salt, but inflammation may be mediated primarily by efferent renal sympathetic nerve activity. Also, resting afferent renal nerve activity is elevated in DOCA salt rats, which may highlight a crucial neural mechanism in the development and maintenance of hypertension. Abstract : Supplemental Digital Content is available in the text.